Pemaknaan riqab sebagai salah satu asnaf zakat di masa sekarang - Najiya, Usluki (Maliki Interdisciplinary Journal, 2024)
Zakat is one of the fourth pillars of Islam, apart from that, zakat is also a form of worship that provides socio-economic balance for Muslims. There are two types of zakat in Islam, namely, zakat mal and zakat fitrah. In practice, zakat mal is carried out after reaching one haul, while zakat fitrah is carried out at the end of each month of Ramadan. In ancient times, the riqab as one of the groups receiving zakat was greatly helped by the implementation of zakat. Slavery in the past was a social product that was very common without considering the human side. This writing uses a type of library research. The data used is in the form of results, tracing literature obtained from journals, books, theses, documents. In QS. At Taubah verse 60 it is clearly stated that there are 8 groups of zakat recipients, namely the needy, poor, amil zakat, converts, gharim, riqab, fisabilillah, and ibn sabil. With the arrival of Islam, the system of slavery slowly disappeared. With the disappearance of slavery over time, it is necessary to expand the meaning of the riqab itself. The conclusion of this research is that it is necessary to expand the meaning of the meaning of the riqab itself, considering the system of slavery which has now disappeared.